Navigational chart of the Arctic Basin / prepared by the American Geographical Society of New York - American Geographical Society of New York (American Geographical Society of New York, 1926)
Annotated in ink and pencil to show the course of Wilkins' 2100 mile flight done with Lt. Ben Eilson from Pt. Barrow, Alaska to Spitsbergen, Norway in 1928 for which accomplishment Wilkins was knighted by King George V. "Map from which a lantern slide was made, 1928. Slide in collection in archives" -- written in pencil in bottom margin. Color